A New Physical Layer Security Scheme Based on Adaptive Bit Channel Selection for Polar-Coded OFDM - Yuki Kuraya; Hideki Ochiai (IEEE Open Journal of Vehicular Technology)
We propose a new physical layer security scheme for a wiretap channel in polar-coded OFDM-based wireless communication systems. Our approach is based on the adaptive bit channel selection, where the input bit channels of polar code are selected according to the frequency selectivity of the main channel. Specifically, the polar code is constructed by the legitimate receiver based on its observed channel state information (CSI), and the receiver informs the transmitter of the resulting code structure. Since the proposed scheme attempts to improve the block error rate (BLER) performance exclusively for the main channel, it provides a significant performance gain over the wiretap channel, as long as the channel of the eavesdropper is not highly correlated with that of the legitimate receiver. On the assumption that the wiretap channel is uncorrelated with the main channel, simulation results demonstrate that the main channel can achieve significant performance gains over the wiretap channel, even under the worst-case scenario where the selected polar code structure (i.e., a set of the bit channels selected by the legitimate receiver for information transmission) is completely known to the eavesdropper. We also consider the case where the main channel and wiretap channel are correlated and reveal that our approach is effective even in the presence of mild channel correlation. Finally, the effect of the channel estimation error on the resulting BLER is also examined, pointing out the importance of accurate CSI acquisition at the receiver side.